Cultural and public services as factors of city resilience? Evidence from big plant closures and downsizing - Kristian Behrens; Manassé Drabo; Florian Mayneris (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2021)
We combine census and establishment-level data for 2001-2017 to study the impact of mass layoffs of big manufacturing plants on city-level population and its composition in Canada. We find that manufacturing plant closures and downsizing lead to a decline in subsequent population growth, especially among the young, those of working age, migrants, and the less skilled. There are also sizable negative effects on the local employment in other industries, which can explain why such negative local labor demand shocks affect population dynamics. Public services (health and education) and cultural and recreational amenities are shown to make cities more resilient and help them retain population following negative local labor demand shocks.
Keywords: J10; R11; R12; R23; 330; Socio-demographic change; plant closures; downsizing; manufacturing; city resilience